2019
DOI: 10.21608/jenvbs.2019.6002.1036
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Rhizobacteria enhance Onion (Allium cepa L.) productivity and minimize requisite chemical fertilization

Abstract: A FIELD experiment was carried out on the farm of Faculty of Agriculture, Mansoura University, Mansoura, Egypt during the winter season of 2016 to study the effect of bio-fertilization under different level of nitrogen and potassium (75% and 50% from the full dose) on the growth and yield of Onion plants. The obtained results showed that the microbial inoculation leads to a significant increase in growth parameters (foliage heights, number of leaves and dry weights). As well as NPK-contents as responded to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…These results were in harmony with those obtained by Hauka et al [92], who found that the mixed inoculum of Azotobacter, Azospirillum, cyanobacteria, and AMF in the presence of compost as organic fertilizer recorded the highest number of total bacteria, such as Azotobacter, Azospirillum, and cyanobacteria, as well as increased the mycorrhizal infection. Similarly, the bio-fertilization has increased the microbial count as compared with the mineral fertilization as observed in wheat [62] and in onion [63].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These results were in harmony with those obtained by Hauka et al [92], who found that the mixed inoculum of Azotobacter, Azospirillum, cyanobacteria, and AMF in the presence of compost as organic fertilizer recorded the highest number of total bacteria, such as Azotobacter, Azospirillum, and cyanobacteria, as well as increased the mycorrhizal infection. Similarly, the bio-fertilization has increased the microbial count as compared with the mineral fertilization as observed in wheat [62] and in onion [63].…”
Section: Discussionmentioning
confidence: 89%
“…The effective role of biofertilizer inoculation on plant growth could be related to its ability to produce high quantities of auxin, such as indole acetic acid. Moreover, these microorganisms and AMF have the potential for N fixation, and P and K mobilization, leading to enhanced nutrient uptake and plant growth [61][62][63]. Previous studies also reported that the N-fixing and P-solubilizing bacterial strains had the ability to provide nutrients and stimulate each other through their physical and biochemical activities and, subsequently, enhancing the physiological properties of plants [64].…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth-promoting rhizobacteria (PGPR) include a wide range of soil microbes that can provide plants with different benefits such as nitrogen fixation, phosphate solubilization, potassium release, and phytohormones production, in addition to plant growth promotion [11][12][13][14][15][16][17][18][19]. These microbes can provide essential nutrients to plants, mainly nitrogen, phosphorus, and potassium, which contribute to plant growth promotion and higher yield and minimize the use of chemical fertilizers [20,21]. For example, Bradyrhizobium has an important role in improving the plant growth and yield of several species.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with many previous studies on different crops which recorded similar inoculation effects on soil fertility status [ 34 , 35 ] and on crops. Among those related to onion crops, seed treatment with inoculation of Azotobacter chroococcum MF135558 and adhesive agents, in the presence of a 75% dose of NK, improved the growth and yield of plants in a field experiment [ 36 ]. Samayoa et al [ 37 ] reported effective isolation and reinoculation of Leifsonia sp., Bacillus megaterium , and Pantoea sp.…”
Section: Discussionmentioning
confidence: 99%